Evaluating employees’ perceptions of non-monetary incentives in workplace-based weight loss programs - Adriana Aparecida de Oliveira-Barbosa; PINHEIRO FERNANDES, ANNA CHRISTINA; QUINTILIANO SCARPELLI DOURADO , DAIANA APARECIDA; Maria Rita Marques de Oliveira; Julieta Belmar Prieto; MASFERRER RIQUELME, DOMINIQUE ANDREA (Sociedad Chilena de Nutricion, 2025)
This study investigated Chilean employees expectations, perceptions of acceptability, and beliefs about the potential effectiveness of non-monetary incentives in workplace weight loss programs. Eighty-six employees with overweight and sedentary occupations from six Chilean companies participated in 16 focus groups as part of a descriptive qualitative study. The content analysis, grounded in Self-Determination Theory, revealed eight categories grouped into three overarching themes: 1) Beliefs and challenges regarding healthy habits and body weight. 2) Workplace structure, environment, and culture. 3) The use of non-monetary incentives to promote healthy behaviors at work. While participants appreciated the non-monetary incentives, these were not enough to overcome the psychological, emotional, and structural barriers to adopting healthier lifestyles. Non-monetary incentives that provided additional spare time, particularly for family, were the most appreciated by participants; nevertheless, organizational constraints restrict the use of these incentives in workplace weight loss initiatives. In conclusion, although non-monetary incentives were identified as a strategy to promote healthier lifestyles, their success is dependent on implementing structural and cultural modifications in the work environment. A comprehensive strategy that considers both individual and organizational factors is needed to promote sustainable healthy habits.